Can I Lie? Childrens’ perspective - Martins, Dulce (2012)
Our study is centered on children lie theme. We carried it out in elementary school of Lisbon district, with children between 10 to 14 years old. The aim of the current study was to understand what children in these ages recognize as a lie. We have thus investigated, in the participating students (N= 93) how these children define a lie, if it is or is not acceptable in their point of view and if a liar deserves punishment as a consequence of a lie. To achieve this, we carried out a qualitative and interpretative investigation where, through an open questionnaire with four stories adapted from previous work by Piaget (1932).